Cognitive -behavioral therapy for managing depressive and anxiety symptoms after stroke: a systematic review and meta-analysis. Issue 4 (19th May 2023) - Ahrens, Jessica; Shao, Richard; Blackport, Daymon; Macaluso, Steven; Viana, Ricardo; Teasell, Robert; Mehta, Swati
ABSTRACT: Background: Post-stroke anxiety and depression can be disabling and result in impaired recovery. Cognitive-behavioral therapy (CBT) has been demonstrated to be effective for anxiety and depression; however, determining its efficacy among those with stroke is warranted. Our objectives to evaluate CBT for anxiety and depression post-stroke . Methods: This review was registered with PROSPERO (REG# CRD42020186324). Medline, PsycInfo, and EMBR Cochrane were used to locate studies published before May 2020, using keywords such as stroke and CBT. A study was included if: (1) interventions were CBT-based, targeting anxiety and/or depression; (2) participants experienced a stroke at least 3 months previous; (3) participants were at least 18 years old. Standardized mean differences ± standard errors and 95% confidence intervals were calculated, and heterogeneity was determined. The Cochrane Risk of Bias tool was used. Results: The search yielded 563 articles, of which 10 ( N = 672) were included;6 were randomized controlled trials. Primary reasons for exclusion included: (1) wrong population (2) insufficient data provided for a meta-analysis; (3) wrongoutcomes. CBT showed large effects on reducing overall anxiety (SMD ± SE: 1.01 ± 0.32, p < .001) and depression (SMD ± SE: 0.95 ± 0.22, p < .000) symptoms at the end of the studies. CBT moderately maintained anxiety (SDM ± SE: 0.779 ± 0.348, p ˂.025) and depression (SDM ± SE: 0.622 ± 0.285, p ˂ .029) scores after 3-months. Limitations included small sample size, limited comparators, and lack of follow-up data. Conclusion: The results of this meta-analysis provide substantial evidence for the use of CBTto manage post-stroke anxiety and depression.